(untitled) (Research, Society and Development, 2021)
Down syndrome has biomechanical and structural changes that result in a deficit in muscle activation and, consequently, in balance. In view of this, Virtual Reality emerges as a therapeutic tool, in which users are presented with opportunities to be involved in virtual environments, which adds a motivational and playful factor to rehabilitation. Objective: To verify the effects of Virtual Reality therapy on the balance and muscle activity of lower limbs of children with Down Syndrome. Methods: The sample consisted of individuals with Down Syndrome with a mean age of 10.8 ± 3.4 years, who underwent motor assessments before and after interventions in Virtual Reality therapy using the Nintendo Wii. Results: Medial and lateral displacement (p = 0.016), anteroposterior displacement (p = 0.056) and muscle activity of the anterior tibial muscle (p = 0.001) had significant improvement after therapy. Conclusion: The proposed therapy is efficient and is indicated for improving the balance and muscle activity of lower limbs of children with Down Syndrome.